Biological and clinical review of IORT-induced wound fluid in breast cancer patients - Jeibouei, Shabnam; Shams, Forough; Mohebichamkhorami, Fariba; Sanooghi, Davood; Faal, Bahareh; Akbari, Mohammad Esmaeil; Zali, Hakimeh (Frontiers in Oncology, 2022)
Intraoperative radiotherapy (IORT) has become a growing therapy for early-stage breast cancer (BC). Some studies claim that wound fluid (seroma), a common consequence of surgical excision in the tumor cavity, can reflect the effects of IORT on cancer inhibition. However, further research by our team and other researchers, such as analysis of seroma composition, affected cell lines, and primary tissues in two-dimensional (2D) and three-dimensional (3D) culture systems, clarified that seroma could not address the questions about IORT effectiveness in the surgical site. In this review, we mention the factors involved in tumor recurrence, direct or indirect effects of IORT on BC, and all the studies associated with BC seroma to attain more information about the impact of IORT-induced seroma to make a better decision to remove or remain after surgery and IORT. Finally, we suggest that seroma studies cannot decipher the mechanisms underlying the effectiveness of IORT in BC patients. The question of whether IORT-seroma has a beneficial effect can only be answered in a trial with a clinical endpoint, which is not even ongoing.